2018
DOI: 10.3390/beverages4040096
|View full text |Cite
|
Sign up to set email alerts
|

Wine Polyphenols and Neurodegenerative Diseases: An Update on the Molecular Mechanisms Underpinning Their Protective Effects

Abstract: Alzheimer's and Parkinson's diseases are the most common age-related and predominantly idiopathic neurodegenerative disorders of unknown pathogenesis. Although these diseases differ in their clinical and neuropathological features, they also share some common aetiologies, such as protein aggregation, mitochondrial dysfunction, oxidative stress, and neuroinflammation. Epidemiological, in vitro and in vivo evidences suggest an inverse correlation between wine consumption and the incidence of neurodegenerative di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 157 publications
(181 reference statements)
0
8
0
Order By: Relevance
“…The increased Aβ accumulation following AD can decrease adenosine monophosphateactivated protein kinase (AMPK) activity, decrease cytosolic Ca 2+ -calcium/calmodulin-dependent protein kinase-β phosphorylation (CaMKKβ), increase autophagy activation of the ubiquitin-proteasome system and as a result, break down proteins such as PGC-1α. These factors disrupt the mitochondrial DNA function of neurons and ultimately result in mitochondrial-dependent cell death (4,19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased Aβ accumulation following AD can decrease adenosine monophosphateactivated protein kinase (AMPK) activity, decrease cytosolic Ca 2+ -calcium/calmodulin-dependent protein kinase-β phosphorylation (CaMKKβ), increase autophagy activation of the ubiquitin-proteasome system and as a result, break down proteins such as PGC-1α. These factors disrupt the mitochondrial DNA function of neurons and ultimately result in mitochondrial-dependent cell death (4,19).…”
Section: Discussionmentioning
confidence: 99%
“…Alzheimer's disease is known as a disorder of brain metabolism; the phosphorylation of amyloid precursor protein (APP) appears to increase beta-amyloid (Aβ) and oxidative stress (2). This negatively regulates or decreases the levels of sirtuins and peroxisome proliferatoractivated receptor-γ coactivator (PGC-1α), as well as induces mitochondrial-dependent cell death (2)(3)(4). On the other hand, many studies have reported favorable effects of physical activity on the nervous system function (5,6) so that endurance training (ET) (7) and voluntary training (8) reduced oxidative stress, autophagic factors, and cell death markers and increased mitochondrial biogenesis in the hippocampal tissue of elderly rats.…”
Section: Introductionmentioning
confidence: 99%
“…The mode through which wine consumption may affect the onset of Alzheimer's and Parkinson's diseases has been extensively studied. In the first case, protection may take place through the antioxidant and anti-inflammatory activities of wine, as well as through more specific functions such as the modulation of secretase enzymes, the enhancement of amyloid clearance, the inhibition of amyloid aggregation and the prevention of tau protein hyperphosphorylation [135][136][137]. In-deed, the activation of α-secretase activity by 6% Cabernet Sauvignon, myricetin, quercetin, resveratrol, and caffeic acid [138][139][140][141][142][143], along with the inhibition of BACE1 activity by resveratrol and some of its oligomers, epicatechin, myricetin, quercetin, kaempherol and caffeic acid [142][143][144][145][146][147][148][149][150][151][152][153][154] and inhibition of γ-secretase by resveratrol, oxy-resveratrol, and piceatannol [155,156], have been reported.…”
Section: Functional Properties Of Winementioning
confidence: 99%
“…Since in vitro antioxidant capacity is closely linked to total polyphenol content, white wines exhibit approximately five to ten times lower antioxidant activity than red wines. White wine also contains significant amounts of hydroxycinnamic acids, tyrosol, and hydroxytyrosol, which are known for their antioxidant properties [65,68]. One noteworthy aspect of this diversity is the variation in antioxidant content among the different types of wine.…”
Section: One Food At a Time: Here The Liquid Foodsmentioning
confidence: 99%